2010
DOI: 10.1016/j.bone.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

HO-1 expression increases mesenchymal stem cell-derived osteoblasts but decreases adipocyte lineage

Abstract: Human bone marrow mesenchymal stem cells (MSC) are pleitrophic cells that differentiate to either adipocytes or osteoblasts as a result of cross-talk by specific signaling pathways including heme oxygenase (HO)-1/-2 expression. We examined the effect of inducers of HO-1 expression and inhibitors of HO activity on MSC differentiation to the osteoblast and adipogenesis lineage. HO-1 expression is increased during osteoblast stem cell development, but remains elevated, at 25 days. The increase in HO-1 levels proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 51 publications
8
130
0
Order By: Relevance
“…Adipocyte enlargement is associated with an increase in the release of TNFα, IL-1, IL-6 and increased insulin resistance. [6][7][8]25 Induction of HO-1 has been shown to enhance cell survival and moderate the diabetic state and obesity. [37][38][39] Induction of HO-1 gene expression in vivo and in cell culture is associated with an increase in pre-adipocytes, a reduction in the number of enlarged adipocytes, but an increase in small adipocyte and adiponectin levels.…”
Section: Apoa1mentioning
confidence: 99%
See 1 more Smart Citation
“…Adipocyte enlargement is associated with an increase in the release of TNFα, IL-1, IL-6 and increased insulin resistance. [6][7][8]25 Induction of HO-1 has been shown to enhance cell survival and moderate the diabetic state and obesity. [37][38][39] Induction of HO-1 gene expression in vivo and in cell culture is associated with an increase in pre-adipocytes, a reduction in the number of enlarged adipocytes, but an increase in small adipocyte and adiponectin levels.…”
Section: Apoa1mentioning
confidence: 99%
“…[37][38][39] Induction of HO-1 gene expression in vivo and in cell culture is associated with an increase in pre-adipocytes, a reduction in the number of enlarged adipocytes, but an increase in small adipocyte and adiponectin levels. 8,23,25,40 HO-1 is induced by a broad spectrum of inducers such as statins, curcumin and ApoA1 mimetic peptides 41 and has been shown to play a crucial role in protection against oxidative insult in diabetes and cardiovascular disease. 41 A decrease in HO-1 expression results in increased insulin resistance and adiposity in Zucker rats and ob mice.…”
Section: Apoa1mentioning
confidence: 99%
“…HO-1 can inhibit the maturation and mineralization of rat osteoblast (Lin et al 2010). On the contrary, others reported that HO-1 can increase the osteogenic differentiation of human MSCs (Vanella et al 2010). In addition, the activation of HO-1 regulates osteoclastogenesis and bone reabsorption during fracture repair (Komatsu and Hadjiargyrou 2004).…”
Section: Introductionmentioning
confidence: 99%
“…HO activity was measured as previously described (Vanella et al 2010) with minor modification (Fig. 1A, C).…”
Section: Ho Activity Assaymentioning
confidence: 99%
“…Treatments were limited to mature adipocytes in order to reduce the potential for confounding effects on the differentiation process, as has been reported by others [238,242,276,277], and incubation periods were limited to 24-48 h to reduce the likelihood of secondary effects. As expected, treatment with two widely used inducers of HO-1, CoPP and Hemin, resulted in increased HO-1 expression at both the mRNA and protein level.…”
Section: Discussionmentioning
confidence: 99%